2020
DOI: 10.35848/1882-0786/ab8c1d
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between depolarization temperature and lattice distortion in quenched (Bi1/2Na1/2)TiO3-based ceramics

Abstract: (Bi1/2Na1/2)TiO3 (BNT) is one of the candidates for lead-free piezoelectric ceramics. Recently, we found that the depolarization temperature T d of BNT could be increased by approximately 40 °C–80 °C with a quenching treatment after the sintering. To elucidate the mechanism, high-energy synchrotron X-ray powder diffraction data were collected in SPring-8 to analyze their crystal structures in detail. In the case of a quenched BNT-based sample, Bi ions displaced more to the off-center position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 32 publications
5
40
0
Order By: Relevance
“…In the quenched samples, previous reports reveal that the enhancement of lattice distortion enhances the order of the lattice structure and then stabilizes the structural phase. 29) Our results (Fig. 7) also showed that the lattice distortion was enhanced by quenching, and we considered that the lattice of the quenched samples has a more ordered structure than that of OF-samples.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…In the quenched samples, previous reports reveal that the enhancement of lattice distortion enhances the order of the lattice structure and then stabilizes the structural phase. 29) Our results (Fig. 7) also showed that the lattice distortion was enhanced by quenching, and we considered that the lattice of the quenched samples has a more ordered structure than that of OF-samples.…”
Section: Resultssupporting
confidence: 61%
“…16) Such a contribution of the bonding enhances disorder in the lattice, and then the structural phase of the unit cell changes from R3c to P4bm or Pnma. 16),17),27) 29) The quenching process after sintering is effective to increase the T d of BNT ceramics with the rhombohedral phase and the quenching does not deteriorate their piezoelectric and ferroelectric properties. 30), 31) The T d of BNT ceramics reaches 223°C after quenching from 1100°C, that is, the T d is about 50°C higher than that by the conventional cooling process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 In NBT-6BT, it has been demonstrated that Bi-O and Bi-Ti bond distances feature an abrupt change at T m but not at T F-R , indicating the transformation from rhombohedral to tetragonal phase to occur gradually. However, a recent report indicated that quenching results in enhanced Bi 3+ offcentering as opposed to furnace-cooled specimens, 32 which can alter the local structure. In the present work, it was observed that quenching significantly affects T F-R , but does not alter T m (Figure 3; Table 1) and the quenched compositions exhibit an increased tetragonal distortion.…”
Section: Resultsmentioning
confidence: 99%
“…The unit-cell parameters of K-substituted NBTs were refined by Rietveld analysis and summarized in Table I. Larger isotropic atomic displacement parameters, B, of Na, Bi and K sites may be caused by the displacement of Bi ions on the off-center position along the <111> direction [20].…”
Section: Results and Discussion 31 Phase Identification Of K-substituted Nbtsmentioning
confidence: 99%